2018
DOI: 10.1002/jib.494
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and sensory profiles of Slovenian and Czech hop genotypes in single hopped beers

Abstract: The sensory profile of beer is influenced by the hop variety and hopping technology. This study examined pilot (50 L) pale lager beers, hopped in the kettle with (or without) single dry hopping. Seven Slovenian, four Czech and one American genotypes were used to determine the impact of dry hopping on the sensory and volatile profiles of beer. Descriptive and bitterness lingering assessment sensory methods were used. The essential oil composition of the hops and beers was accessed using GC/MS so as to clarify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…Those studies also defined the dominant aroma compounds with their typical flavours, as well as the method of their detection. On comparing the results with the available literature, it can be stated that samples of dry hopped Kazbek (Mikyška et al, 2018;Krofta et al, 2019), Mandarina Bavaria (Takoi et al, 2016), Amarillo (Van Holle et al, 2017), Cascade and Chinook (Vollmer et al, 2018) reflected the major flavour components of these varieties evoking floral, spicy or citrus flavour.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Those studies also defined the dominant aroma compounds with their typical flavours, as well as the method of their detection. On comparing the results with the available literature, it can be stated that samples of dry hopped Kazbek (Mikyška et al, 2018;Krofta et al, 2019), Mandarina Bavaria (Takoi et al, 2016), Amarillo (Van Holle et al, 2017), Cascade and Chinook (Vollmer et al, 2018) reflected the major flavour components of these varieties evoking floral, spicy or citrus flavour.…”
Section: Resultsmentioning
confidence: 79%
“…The spicy aroma was, in general, the least intensive (1.5-2.7 points) in the evaluation of dry hopped beers. Several studies (Van Holle et al, 2017;Vollmer et al, 2018;Mikyška et al, 2018) reported on the preparation of beers hopped with the same hop varieties as the ones investigated in our study. Those studies also defined the dominant aroma compounds with their typical flavours, as well as the method of their detection.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Anthocyanogens were determined according to the MEBAK Analytics (MEBAK, 2011). The essential oils in hops and beer were determined by the method developed at RIBM (Mikyška et al, 2018). The sensory analysis of beer, including a detailed evaluation of hop aromas, was performed by a descriptive method developed at RIBM and the triangle test of difference.…”
Section: Analysesmentioning
confidence: 99%
“…Beer analyses were performed according to the EBC (EBC Analysis Committee, 2010). The essential oils in beer were determined by the GC/MS method developed at RIBM (Mikyška et al, 2018). Sensory analysis of beer was carried out by a trained sensory panel of RIBM using descriptive methods and triangle test (EBC Analysis Committee, 2010).…”
Section: Kettle Hoppingmentioning
confidence: 99%